Fracture risk is increased in Crohn's disease, but not in ulcerative colitis - Vestergaard, P; Krogh, K; Rejnmark, L; Laurberg, S; Mosekilde, L (Gut, 2000)
AIMS To study fracture rates and risk factors for fractures in patients with Crohn's disease and ulcerative colitis. METHODS 998 self administered questionnaires were issued to members of the Danish Colitis/Crohn Association, and 1000 questionnaires were issued to randomly selected control subjects. 845 patients (84.5%) and 645 controls (65.4%) returned the questionnaire (p<0.01). 817 patients and 635 controls could be analysed. RESULTS Analysis was performed on 383 patients with Crohn's disease (median age 39, range 8–82 years; median age at diagnosis 26, range 1–75 years), 434 patients with ulcerative colitis (median age 39, range 11–86 years; median age at diagnosis 29, range 10–78 years), and 635 controls (median age 43, range 19–93 years, p<0.01). The fracture risk was increased in female patients with Crohn's disease (relative risk (RR) = 2.5, 95% confidence interval (CI) 1.7–3.6), but not in male patients with Crohn's disease (RR = 0.6, 95% CI 0.3–1.3) or in patients with ulcerative colitis (RR = 1.1, 95% CI 0.8–1.6). An increased proportion of low energy fractures was observed in patients with Crohn's disease (15.7% versus 1.4 % in controls, 2p<0.01), but not in patients with ulcerative colitis (5.4%, 2p=0.30). The increased fracture frequency in Crohn's disease was present for fractures of the spine, feet, and toes and fractures of the ribs and pelvis. Fracture risk increased with increasing duration of systemic corticosteroid use in Crohn's disease (2p=0.028), but not in ulcerative colitis (2p=0.50). CONCLUSIONS An increased risk of low energy fractures was observed in female patients with Crohn's disease, but not in male patients with Crohn's disease or in patients with ulcerative colitis.